A new liquid chromatography–quadrupole time of flight‐tandem mass spectrometry method development and validation for identification and ultra‐trace level quantification of genotoxic impurity 1, 3‐diacetoxy‐2‐(acetoxymethoxy) propane in valganciclovir hydrochloride active pharmaceutical ingredient. Issue 3 (19th January 2022) - Moorthy, Manchuri Krishna; Ali, Shaik Mahammad; Reddy, Gopireddy Venkata Subba
Abstract: A new reverse phase and short run time (3.0 min) liquid chromatography–quadrupole time of flight‐tandem mass spectrometry method was developed and validated for identification and ultra‐trace level quantification (0.83 ppm) of genotoxic impurity 1, 3‐diacetoxy‐2‐(acetoxymethoxy) propane in valganciclovir hydrochloride active pharmaceutical ingredient. The method is cost effective, time saving and proficient to confirm the parent and fragment ion masses through mass spectrometry and tandem mass spectrometry further fragmentation. An isocratic program and acquity bridged ethylene hybrid C18 reverse phase column (100 mm × 4.6 mm × 1.7 μm) was used to accomplish optimum separation between valganciclovir and 1, 3‐diacetoxy‐2‐(acetoxymethoxy) propane impurity. Mobile phase‐A used was 0.1% formic acid in milli Q water and mobile phase‐B used was acetonitrile in the ration of 50:50 v/v. Diluent used was water and methanol in the ratio of 30:70 v/v. Chromatographic conditions are selected as injection volume: 3 μL, flow rate: 0.2 mL/min, oven temperature: ambient, auto sampler: 5°C and run time: 3.0 min. The retention time of 1, 3‐diacetoxy‐2‐(acetoxymethoxy) propane impurity was found at 1.830 min. The detection and quantification levels found at 0.027 and 0.083 ppm. The 1, 3‐diacetoxy‐2‐(acetoxymethoxy) propane impurity is linear from 0.082 to 1.236 ppm levels with regression coefficient 0.9972. The recoveries were from 93.3 to 110.0%.